2014
DOI: 10.5371/hp.2014.26.2.107
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Time to Bony Union of Femoral Subtrochanteric Fractures Treated with Intramedullary Devices

Abstract: PurposeTo evaluate the factors affecting the bone union time and the occurrence of nonunion after intramedullary nailing of subtrochanteric femoral fractures in adults.Materials and MethodsWe retrospectively reviewed data from 31 patients (22 men and 9 women) who had undergone femoral intramedullary nailing at least 1 year post-operatively and analyzed the bone union time, nonunion rates, and factors that affected the bone union time according to the fracture classification (AO and Fielding classifications), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…However, use of IMN remains technically demanding and requires proper reduction and correct positioning of the implant [34]. Malreduction in either the coronal (comminution of the medial cortex) or sagittal plane leads to prolonged time to union for subtrochanteric fractures [10, 35, 36]. Percutaneous reduction maneuvers and minimally invasive techniques can be useful in obtaining proper reduction [3].…”
Section: Discussionmentioning
confidence: 99%
“…However, use of IMN remains technically demanding and requires proper reduction and correct positioning of the implant [34]. Malreduction in either the coronal (comminution of the medial cortex) or sagittal plane leads to prolonged time to union for subtrochanteric fractures [10, 35, 36]. Percutaneous reduction maneuvers and minimally invasive techniques can be useful in obtaining proper reduction [3].…”
Section: Discussionmentioning
confidence: 99%
“…The radiological follow-up included anterior–posterior (AP) and lateral radiographs after 6 weeks, 12 weeks, 6 months and additionally 12 months if necessary. Clinically, nonunion was defined as persistent pain at the fracture site during weight bearing after 6 months [3, 10, 21]. Radiologically, nonunion was defined as lack of cortical bridging after 6 months on at least three cortices [3, 4, 12, 21].…”
Section: Methodsmentioning
confidence: 99%
“…13 Therefore, maintenance of the continuity of the medial cortex and the reduction of all possible fracture fragments is recommended. 14 Riehl JT et al 5 showed malreduction greater than or equal to 10 in any plane and Choi JY et al 6 recommended the comminution of the medial cortex and the degree of the postoperative displacement of fractures contributed to fracture non-union. When fracture displacement degree increased, the medial buttress lost more seriously.…”
Section: Discussionmentioning
confidence: 99%
“…Riehl JT et al 5 found there was a statistically significant higher rate of delayed or nonunion when postoperative radiographs showed malreduction greater than or equal to 10 in any plane. Choi JY et al 6 recommended the comminution of the medial cortex and the degree of the postoperative displacement of fractures contributed to the delayed time of union. However, there was no further research about fracture non-union with fracture displacement degree in current studies.…”
Section: Introductionmentioning
confidence: 99%